Determination of Economic Packaging Frequency for Items Jointly Replenished - Goyal, S. K. (Management Science, 1973)
The model described in this paper is typically applicable to the batch processing industry where a batch of a product is packaged into several container types immediately after manufacture. An example involving 10 jointly replenished items has been solved for illustrating the recommended approach.